Respostas
respondido por:
1
x+y=-7
x-y=6
2x=-1
x=-1/2
x+y=-7 (-1)
x-y=6
-x-y=+7
x-y=6
-2y=13
2y=-13
y=-13/2
B)
m+n=4 *(-1)
3m+n=2
-m-n=-4
3m+n=2
2m=-2
m=-2/2
m=-1
m+n=4 *(-3)
3m+n=2
-3m-3n=-12
3m+n=2
-2n=-10 (-1)
2n=10
n=10/2
n=5
x-y=6
2x=-1
x=-1/2
x+y=-7 (-1)
x-y=6
-x-y=+7
x-y=6
-2y=13
2y=-13
y=-13/2
B)
m+n=4 *(-1)
3m+n=2
-m-n=-4
3m+n=2
2m=-2
m=-2/2
m=-1
m+n=4 *(-3)
3m+n=2
-3m-3n=-12
3m+n=2
-2n=-10 (-1)
2n=10
n=10/2
n=5
belltorresteixeira:
vlw
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás